(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper provides spherically symmetric solution of Einstein’s field equations for the perfect fluid with equation of state p = a, where a [0, 1] has been obtained taking suitable choice of g11 or g44 (e.g. ). Many previously known solutions are contained herein as a particular case. Various physical and geometrical properties have been also studied.